Impact of ISO 9001 Certification on the Projects Success of Large-Scale (AAA) Construction Firms in the Philippines - Neyestani, Behnam (International Research Journal of Management, IT & Social Sciences, 2016)
The general purpose of this study is to investigate the effects of ISO 9001 certification on project success, and its main criteria into large-scale construction companies in Metro Manila, Philippines. For this aim, the research was conducted an in-depth literature review for identifying the main variables first. Subsequently, a survey questionnaire was designed, and distributed randomly among 67 managers working in ISO 9001:2008-certified projects of large-scale construction firms. Then the descriptive and inferential statistics analysis employed, in order to find the results and conclusions. Finally, the findings revealed that ISO 9001 certification can significatly affect the construction project success and its main criteria, except time lenght of projects in Metro Manila, Philippines.